Accuracy of Focused Assessment with Sonography in Trauma (FAST) In Detecting Visceral Injury Following Blunt Trauma with Computed Tomography (Ct) as A Gold Standard: FAST In Detecting Visceral Injury Following Blunt Trauma with Ct - Qureshi, Saad Saleem; Burhan, Dawar; Zubair, Nashmia; Samnani, Saira; Shahid, Minaa (Pakistan Journal of Health Sciences, 2026)
Blunt abdominal trauma is one of the major causes of morbidity and mortality around the world. The prompt identification of visceral damage is crucial for effective management, and FAST is a proven, widely adopted first-line imaging tool. Objectives: To investigate the diagnostic value of FAST for ascertaining the presence of visceral injuries after blunt abdominal injury, keeping the CT scan as the reference measure. Methods: A cross-sectional study was implemented at the Department of Radiology, Aga Khan University Hospital, Karachi, from June 2025 to September 2025. A population of 103 patients meeting eligibility criteria with blunt abdominal trauma was selected by non-probability consecutive sampling. FAST was performed on all patients, with the findings subsequently correlated with subsequent CT scans. A 2x2 contingency table in which the CT scan served as the gold standard was used to estimate sensitivity, specificity, positive and negative predictive values of FAST, and its diagnostic accuracy. SPSS version 26.0 was used to analyze data using the Shapiro-Wilk test. Results: FAST had a sensitivity of 88.24% and a specificity of 81.16%. Total diagnostic accuracy was 83.50%. The PPV was 69.77% and the NPV 93.33%. FAST was noted to be highly efficient for detecting intra-abdominal injuries; however, some false positives were also reported. Conclusions: FAST is a non-invasive, diagnostic measure as a preliminary assessment of blunt abdominal trauma with a good sensitivity and NPV, and hence turns out to be a useful screening test, particularly in resource-limited and emergency settings.